Estrategias para la internacionalización de las PYMES del sector manufacturero en la ciudad de Barranquilla (2020)
In a dynamic and changing world where global trends show consumers increasingly demanding in their preferences, it is necessary for companies to prioritize these needs and provide products and services that are at the forefront in the market. In this way, these are the economic base for the development of the countries, therefore, they require a higher level of competitiveness and even more so when their processes facilitate interactions with the world environment. The foregoing indicates that it would be convenient to delve into the structure of companies such as SMEs, so that barriers are reduced to boost their growth through internationalization strategies that in the future allow them to transcend to new markets. The results show that the strategies used must be developed from the point of view of each stage of the internationalization process of SMEs, among which the self-evaluation of the company, knowledge of the markets, export plan, networks of contacts, product-oriented marketing strategies, among others and will increase in complexity according to the degree of internationalization and experience acquired by the company.